2007
DOI: 10.1002/jts.20234
|View full text |Cite
|
Sign up to set email alerts
|

PTSD symptoms, life events, and unit cohesion in U.S. soldiers: Baseline findings from the neurocognition deployment health study

Abstract: Relationships among a modifiable situational factor (unit cohesion), prior stressful life events, and posttraumatic stress disorder (PTSD) symptoms were assessed in 1,579 U.S. Army soldiers with no history of contemporary war zone deployment. It was predicted that unit cohesion would attenuate the dose-response relationship between past stressor exposures and PTSD symptoms at relatively moderate levels of exposure. Consistent with this hypothesis, regression analysis revealed that life experiences and unit coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 31 publications
10
112
0
6
Order By: Relevance
“…This is consistent with existing literature [28,63,64,82,102,118,133,139,163,167]. Further, low levels of cohesion were more strongly associated with poorer health than were moderate or high levels of unit cohesion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with existing literature [28,63,64,82,102,118,133,139,163,167]. Further, low levels of cohesion were more strongly associated with poorer health than were moderate or high levels of unit cohesion.…”
Section: Discussionsupporting
confidence: 92%
“…Studies of the UK and the US defence forces have identified unit cohesion as a potential factor which can buffer against negative psychological health outcomes after deployment, such as symptoms of posttraumatic stress [28,63,64,102,139,163,167], depression [139,167], and common mental disorders [64,82,133].…”
Section: Introductionmentioning
confidence: 99%
“…A previous quantitative study by Brailey and colleagues found that unit cohesion had a strong impact on life experiences among people with PTSD (Brailey, Vasterling, Proctor, Constans, & Friedman, 2007). These results go in line with the stress-buffering model of social ties and mental health, stating that perceived support prevents negative emotional responses.…”
Section: How Might the Transformation Of Social Capital And Voluntarysupporting
confidence: 70%
“…Resiliency also may be built through increased resources developed while in the military. 40 Resiliency and coping strategies among women veterans warrant further study-particularly through qualitative methods-to better understand the unique situations that may inform a phenomenon such as resiliency in the context of traumatic histories.…”
Section: Discussionmentioning
confidence: 99%